FEATURES OF PREGNANCY IN THE PRESENCE OF RESUS NEGATIVE BLOOD - Sattarova, K.A.; Babadjanova, G.S.; Rakhmanov, Z.Kh. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Modern practice in managing pregnancies in women with Rh immunization is based on comprehensive diagnostics, including determining the Rh status of the mother and father, thoroughly studying the patient’s history, using dopplerometry, and minimizing invasive interventions. The purpose of this work is to analyze the Rh phenotype of the mother and child to assess the likelihood of developing hemolytic disease in the fetus and newborn.